Wormhole-Like Mesoporous Carbons from Gelatine as Multistep Infiltration Effect - Maria Ulfa; Wega Trisunaryanti; Iip Izul Falah; Indriana Kartini (Indonesian Journal of Chemistry, 2016)
Wormhole-like mesoporous carbon from gelatine (WMCG) with two different pore diameters have been synthesized by adopting a modified infiltration treatment. The infiltration effect on the morphology was investigated. The results show that the WMCG sample was obtained after dehydration, pyrolysis and silica removal process. The pore diameters WMCG are 15.2 and 4.8 nm with specific surface areas of 280 m2/g, total pore volumes of 0.5 cm3/g and the thermal stability up to 1400 °C. The bimodal pore of WMCG obtained as the high step of infiltration level effect.